Enhancement of musculocutaneous nerve reinnervation after vascular endothelial growth factor (VEGF) gene therapy - Haninec, Pavel; Kaiser, Radek; Bobek, Vladimír; Dubový, Petr (BMC neuroscience, 2012)
BACKGROUND: Vascular endothelial growth factor (VEGF) is not only a potent angiogenic factor but it also promotes axonal outgrowth and proliferation of Schwann cells. The aim of the present study was to quantitatively assess reinnervation of musculocutaneous nerve (MCN) stumps using motor and primary sensory neurons after plasmid phVEGF transfection and end-to-end (ETE) or end-to-side (ETS) neurorrhaphy. The distal stump of rat transected MCN, was transfected with plasmid phVEGF, plasmid alone or treated with vehiculum and reinnervated following ETE or ETS neurorrhaphy for 2 months. The number of motor and dorsal root ganglia neurons reinnervating the MCN stump was estimated following their retrograde labeling with Fluoro-Ruby and Fluoro-Emerald. Reinnervation of the MCN stumps was assessed based on density, diameter and myelin sheath thickness of regenerated axons, grooming test and the wet weight index of the biceps brachii muscles. RESULTS: Immunohistochemical detection under the same conditions revealed increased VEGF in the Schwann cells of the MCN stumps transfected with the plasmid phVEGF, as opposed to control stumps transfected with only the plasmid or treated with vehiculum. The MCN stumps transfected with the plasmid phVEGF were reinnervated by moderately higher numbers of motor and sensory neurons after ETE neurorrhaphy compared with control stumps. However, morphometric quality of myelinated axons, grooming test and the wet weight index were significantly better in the MCN plasmid phVEGF transfected stumps. The ETS neurorrhaphy of the MCN plasmid phVEGF transfected stumps in comparison with control stumps resulted in significant elevation of motor and sensory neurons that reinnervated the MCN. Especially noteworthy was the increased numbers of neurons that sent out collateral sprouts into the MCN stumps. Similarly to ETE neurorrhaphy, phVEGF transfection resulted in significantly higher morphometric quality of myelinated axons, behavioral test and the wet weight index of the biceps brachii muscles. CONCLUSION: Our results showed that plasmid phVEGF transfection of MCN stumps could induce an increase in VEGF protein in Schwann cells, which resulted in higher quality axon reinnervation after both ETE and ETS neurorrhaphy. This was also associated with a better wet weight biceps brachii muscle index and functional tests than in control rats.
Keywords: Animals; genetická terapie; Female; nemoci periferního nervového systému; Fluoresceins; Musculocutaneous Nerve; Rats, Wistar; Spinal Cord; Peripheral Nervous System Diseases; ženské pohlaví; Organ Size; vaskulární endoteliální růstový faktor A; Neurologic Examination; Nerve Fibers, Myelinated; mícha; Vascular Endothelial Growth Factor A; neurony; Dextrans; neurologické vyšetření; dextrany; regenerace nervu; Nerve Regeneration; Neurons; velikost orgánu; modely nemocí na zvířatech; nervus musculocutaneus; fluoresceiny; Disease Models, Animal; rhodaminy; krysa rodu Rattus; Genetic Therapy; zvířata; nervová vlákna myelinizovaná; Rats; přední končetina; Forelimb; Rhodamines; potkani Wistar